IMPLEMENTASI MANAJEMEN RISIKO KEJAHATAN PERAMPOKAN PADA PENGIRIMAN UANG TUNAI (Studi Kasus Pengiriman Hasil Pendapatan PT ABC Cabang X) - Bunga Mareti (Jurnal Kriminologi Indonesia, 2010)
The purpose of this research is to describe the implementation of robbery crime risk management in cash delivery, especially in relation to income delivery of PT ABC Branch of X, which is an Indonesian Highway Corporation. The result shows that PT ABC has been implementing crime risk management in its income delivery. PT ABC decided on risk transfer methods. It is the transferring of income to tol collection bank, which is Bank XYZ Branch of A, and cash in transit insurance. Because of lack in human resources, Bank XYZ transfers the operationalization to PT KJA. This methods is cost effective, because of the compensation of PT ABC’s role as costumer of Bank XYZ. In its operationalization, PT ABC found the barrier to control it directly. Controlling its operation will be easier to reach if toll collection bank could operationalize independently. Hopefully, crime risk management methods could be applied by other companies which its business characteristics is similar with PT ABC, to reach cost efficiency.